The Assyrian Army and its Soldier, 9th-7th C. B.C. - Henshaw, Richard A. (1969)
The Time of the Start of the Army’s Campaign; The Place of the Start of the Army’s Campaign: The Size of the Army; Functions in the Army: A. The Chariot. B. The Mounted Soldier. C. The Foot Soldier. D. Engineer, sapper, pioneer, messenger. E. The Scribe. F. Officers.